Reliability as a criterion of efficiency of diagnostics of transport and technological machines - Aleksej Nikolaevich Cheboksarov (Вестник СибАДИ)
This article discusses various efficiency criteria for diagnosis of transport and technological machines. As the main criterion it is proposed to use the reliability of technical diagnostics, which can be evaluated by the probability of a correct diagnosis or error. The errors in turn are subdivided into errors of the first and second kind, which have statistical nature and depend on various factors.